Measuring Service Quality for Bakeries in Central Jakarta using the CSI and IPA Methods: Measuring Service Quality for Bakeries in Central Jakarta using the CSI and IPA Methods - Rahayu, Fuji; Herlina, Herlina; Wijaya, Maekel Tan (Universitas Nahdlatul Ulama Surabaya, 2025)
One of the companies engaged in the food industry (bakery) which is well known to many people in Indonesia is PT. Mustika Citra Rasa or better known as Holland Bakery. The results of the GMP audit show that the average GMP value for the Holland Bakery counter in the Central Jakarta area is below 75% which is the standard for the Holland Bakery company. Therefore, research is needed to determine customer satisfaction and improvements that need to be made for customer satisfaction. This study uses the Customer Satisfaction Index (CSI) method to identify customer satisfaction, the Servqual method identifies attribute gaps that cause dissatisfaction with service implementation, the Importance Performance Analysis (IPA) method to determine the variables that need improvement by dividing them on a Cartesian diagram. This study shows that customer satisfaction is in the satisfied category with an index value of 80.64%, obtained 14 attributes have a negative gap, 9 attributes are in quadrant I and 1 attribute is in quadrant III, the order of priority in improving service quality for 10 attributes that are in the priority quadrant, and SOPs that can be carried out to overcome the causes of problems or improve service quality.